(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Antibiotic resistance is a global menace, as the percentage of resistance globally is increasing day by day. The decrease in developing new antimicrobial substances and increase in irrational use of antibiotics supported the emergence of antibiotic resistance. Carbepenem is said to be the priority antibiotic for the treatment of infections caused by gram-negative bacteria. But due to the excessive use, irrational use of this antibiotic and unhygienic environment of hospitals results in the dissemination of carbepenem resistance. Our study reviewed on the resistance mechanisms, reasons of the resiatnce development and global prevalence of carbepenem resiatance